Women's Facial Redness Increases Their Perceived Attractiveness: Mediation Through Perceived Healthiness. (July 2016) - Pazda, Adam D.; Thorstenson, Christopher A.; Elliot, Andrew J.; Perrett, David I.
In the present research, we investigated whether the red-attraction relation that has been observed for men viewing women may also be observed with regard to women's facial redness. We manipulated facial redness by slightly increasing or decreasing the redness on the faces of baseline pictures of target women, and then had men judge the attractiveness of the women. We also examined healthiness perceptions as a mediator of the redness-attraction relation, along with several other candidate mediator variables. A series of experiments showed that increased redness led to increased ratings of attractiveness, and decreased redness led to decreased ratings of attractiveness. Perceived healthiness was documented as a mediator of the influence of female facial redness on male perceptions of attractiveness, and this mediation was independent of other candidate mediator variables. The findings highlight the importance of attending to facial coloration as an attraction-relevant cue and point to interesting areas for subsequent research.